47.1k views
0 votes
G(x) = 2x^3+ 2x^2– 4x – 9
find g(-3)

2 Answers

4 votes

Answer:

-33

Explanation:

I hope this is correct, and I apologize in advance if it isn't :(

User David Okwii
by
5.2k points
3 votes

Answer:

g(-3) = -33

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

g(x) = 2x³ + 2x² - 4x - 9

g(-3) is x = -3

Step 2: Evaluate

  1. Substitute: g(-3) = 2(-3)³ + 2(-3)² - 4(-3) - 9
  2. Exponents: g(-3) = 2(-27) + 2(9) - 4(-3) - 9
  3. Multiply: g(-3) = -54 + 18 + 12 - 9
  4. Add: g(-3) = -36 + 12 - 9
  5. Add: g(-3) = -24 - 9
  6. Subtract: g(-3) = -33
User Jtalarico
by
5.8k points